Diurnal variation of stratospheric short-lived species - Khosravi, Maryam (2012)
Diurnal variation of stratospheric short-lived speciesMaryam KhosraviChalmers University of TechnologyDepartment of Earth and Space SciencesAbstractThe depletion of ozone in the stratosphere has a direct impact on the amount of ultravioletradiation reaching the Earth’s surface. The ozone abundance and distributionis controlled by the photo-chemical reactions and catalytic cycles involving halogens(chlorine and bromine), odd hydrogen and odd nitrogen species as well as by atmospherictransport.An introduction to ozone related chemistry of the stratosphere and modelling ofshort-lived species using photo-chemical models is presented. A one dimensional (1D)atmospheric model is used in two distinct studies: modeling of short-lived species inthe Arctic lower stratosphere (paper I) and in the tropical mid to upper stratosphere(paper II).The first part of this thesis describes the diurnal variation of chlorine monoxide,ClO, which is the most important short-lived species controlling ozone in the polarlower stratosphere during winter and early-spring. The ClO-dimer cycle, involvingClO and its nighttime reservoir Cl2O2, contributes to about 75%of the polar ozone loss.ClO measurements from an airborne submillimeter radiometer in the Arctic twilighthave been compared with the results from a 1D photo-chemical model (MISU-1D), inorder to validate the model and to test the kinetics of the reactions controlling the partitioningof chlorine species during the course of a day. The results show that crosssections leading to faster photolysis rates of Cl2O2 match best with the ClO observations.This is consistent with the recent version of the chemical kinetics evaluation bythe Jet Propulsion Laboratory. Slower photolysis rates can not be reconciled with theobservations since active chlorine higher than the total available chlorine would be required.The model reproduces higher nighttime ClO than the observations, howeverthe nighttime ClOmodelled using recent JPL recommendations of the thermal equilibriumconstant agree within the ...